Shop Drawing Workshop for cadets of Fisheries Mechanization Study Program Sorong Polytechnic of Marine and Fisheries Using Autocad: Peningkatan Softskill Melalui Workshop Pembuatan Shop Drawing Untuk Taruna Prodi Mekanisasi Perikanan Politeknik Kp Sorong Menggunakan Autocad - Yani Nurita Purnawanti; Nurul Huda; Akhmad Nurfauzi; djoko prasetyo; Egbert Joshua Sirait (Politeknik Kelautan dan Perikanan Sorong, 2022)
The lack of competence of Sorong Marine and Fisheries Polytechnic cadets in the field of drawing techniques is one of the causes of the low absorption of graduates in the field of engineering, where the Fisheries Mechanization study program has a curriculum syllabus that is suitable for various engineering industries such as shipbuilding, food processing machinery, ship machinery factories, fishing gear factory, pump factory. While the technical drawing courses taught in the fishery mechanization study program are still limited to manual drawings with paper, as well as tasks in other courses in the form of drawings are also still carried out by manual drawing processes, while technical drawings in industry require accuracy and speed which are difficult to rely on. manual drawing techniques. AutoCad software is one of the computer applications that is considered very effective as a tool in learning and improving students' understanding of technical drawing. Activation of the legal licensed AutoCAD software is expensive, so in this Community Service activity, the AutoCad free Student License activation is carried out, in addition to providing an increase in the soft skills of cadets. The stages of activities in this PKM are: computer inventory in the KP Sorong Polytechnic Computer laboratory, registering the official Autocad student version license for computers in the KP Sorong Polytechnic Computer laboratory, installation & activation of Autocad software on computers in the KP Sorong Polytechnic Computer laboratory, Autocad training for cadets Fisheries Mechanization Study Program KP Sorong Polytechnic, and evaluation of Autocad training for cadets of the Fisheries Mechanization Study Program at KP Sorong Polytechnic. The results achieved are the activation of the AutoCad software with a student license on 34 computers in the computer and telematics lab of the KP Sorong Polytechnic, as well as the improvement in the soft skills of cadets in making shop drawings that can be measured through evaluation, namely as many as 13 cadets passed the training with 8 cadets getting value over 75.